Innovative experimental setup for X-ray imaging to study energetic magnetized plasmas. (2nd March 2021) - Biri, S.; Rácz, R.; Perduk, Z.; Pálinkás, J.; Naselli, E.; Mazzaglia, M.; Torrisi, G.; Castro, G.; Celona, L.; Gammino, S.; Galatá, A.; Romano, F.P.; et al.
Abstract: The research of magnetically confined plasmas with high energy content is nowadays an important branch of the plasma physics with several options considering the chosen technics. One of the ways is the detection of photons emitted by the plasma itself. A new experimental setup was built in the ECR Laboratory of Atomki (Debrecen, Hungary) to detect in 2D the dense EM-radiation emitted by the ECR-plasma. The main elements of the setup are: an ECR ion source (as plasma source, operating at 13.6–14.6 GHz RF pumping frequency) and a pinhole X-ray camera (operating in the 500 eV–20 keV energy domain). An innovative lead collimator system was designed and built between the plasma and the camera. As a result, it has been possible to acquire X-ray pictures up to 200 W total incident RF-power. This value represents the highest operative RF power for which X-ray imaging has been acquired in the field of ECR Ion Sources and ECR compact traps. A new treatment for the noise reduction was applied to study plasma morphology. The new setup gives opportunity not just to study energetic stable plasmas, but even plasma turbulences and instabilities.